Pengaruh Ketidakpastian Lingkungan, Kebijakan Utang, Ukuran Perusahaan, Struktur Kepemilikan, Dan Koneksi Politik Terhadap Tax Avoidance - Wati Tri Utami; Erma Setiawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Environmental Uncertainty, Debt Policy, Firm Size, Ownership Structure, and Political Connections on Tax Avoidance in manufacturing companies within the Property & Real Estate subsector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This research employs a quantitative approach using secondary data obtained from financial reports. The sample was selected using a purposive sampling method based on specific criteria. The dependent variable, Tax Avoidance, is measured using the Effective Tax Rate (ETR), while the independent variables include Environmental Uncertainty, Debt Policy, Firm Size, Ownership Structure, and Political Connections. Data analysis was conducted using multiple linear regression with SPSS, including descriptive statistics, classical assumption tests, and hypothesis testing. The results indicate that only Ownership Structure significantly influences Tax Avoidance, while other variables do not show a significant effect. The limitations of this study include a narrow subsector focus, the exclusion of other potential determinants of tax avoidance, and the limited research period from 2019 to 2023. Future research is recommended to expand sector coverage, incorporate additional variables, and extend the research period to enhance the comprehensiveness of the findings.